(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This study is dedicated to the analysis of the drying process energy consumption. In order to evaluate the main energetic processes that consume the most energy, the energy consumption of each individual drying process with and without air recirculation was modelled. The model shows that drying agent (air) recirculation is not an energy-saving operation, since it increases the total electricity and heat consumption. Recirculation of the drying agent increases the moisture content of the drying agent at the dryer entrance, which increases the need for fresh air in the dryer so that it can absorb the evaporating moisture from the dried material. An increased flow of the drying agent in the dryer increases the heat and electricity consumption.